Mn(OAc)3*2H2O promoted addition of arylboronic acids to quinoxalin-2-ones. Issue 7 (14th February 2018) - Ramesh, Boora; Reddy, C. Ravikumar; Kumar, G. Ravi; Reddy, B.V. Subba
Graphical abstract: Highlights: This is the first report using Mn(OAc)3 . Describes the addition of aryl boronic acids to cyclic imines. This method is cost effective and operationally simple. It is compatible with various functional groups. This method works with a diverse range of substrates. Abstract: A simple method has been developed for the synthesis of 3-aryl quinoxalin-2-one derivatives through an oxidative cross-coupling of arylboronic acids with quinoxalin-2-ones using a readily available oxidant Mn(III) acetate dihydrate. This method provides 3-aryl quinoxalin-2-one scaffolds with a broad substrate scope.